2017
DOI: 10.4103/pr.pr_141_16
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antidiabetic activity of polar and nonpolar solvent extracts from Leucas Aspera (Willd.) link leaves

Abstract: Background:Diabetes mellitus is a chronic illness, and the management of diabetes is a global problem. Successful treatment is required to prevent complications and organ damages. Herbal medicines are having minimal adverse effects when compared to the available synthetic drugs to treat such chronic diseases and disorders.Objective:The present study was aimed to evaluate the antidiabetic and antioxidant activity of polar and nonpolar solvent extracts of Leucas aspera (Willd.) link leaves under in vitro models.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The most prevalent tissue in the body, skeletal muscle, is primarily responsible for the postprandial consumption of glucose [16].…”
Section: Discussionmentioning
confidence: 99%
“…The most prevalent tissue in the body, skeletal muscle, is primarily responsible for the postprandial consumption of glucose [16].…”
Section: Discussionmentioning
confidence: 99%
“…The anti-diabetic activities of Achillea santolina (Grover et al, 2002), Adiantum capillus-veneris (Al-Snafi, 2013), Agrimony eupatoria (Al-Snafi, 2015), Aristolochia longa (El Omari et al, 2019), Atractylis gummifera (Bouabid et al, 2019), Eruca sativa (Kishore et al, 2017), Gaultheria trichophylla (Alam and Saqib, 2017), Leucas aspera (Annapandian and Sundaram, 2017), Myrica gale, Rhodiola rosea, Rumex acetosa, Taraxacum officinale (Sekhon-Loodu and Rupasinghe, 2019), Trixis angustifolia (Salazar-Gómez et al, 2019) and Urtica dioica (Ahangarpour et al, 2012) have been reported. um phosphate dibasic, DPPH (2, 2-diphenyl-1-picrylhydrazyl), ABTS•+ (2,2-azinobis (3-ethyl-benzothiazoline)-6-sulfonic acid disodium salt), hydrogen peroxide, amylase, DNS (dinitrosalicylic) acid, sea salts, glucophage, potassium persulfate were of analytical grade.…”
Section: Introductionmentioning
confidence: 99%